Wiki-mediated Collaborative/Distributed Narrative Construction of Game Communities - Ang, Chee Siang; Zaphiris, Panayiotis; Wilson, Stephanie (My University, 2009)
The paper looks at how Wiki technologies can be used to facilitate language learning among the youth through game playing as a social activity. Constructionism as related to computer games and language learning are examined. Constructionist theory creates a context of learning in which learners become engaged in collaborative construction of sharable and meaningful artefacts. A case study of narrative construction is investigated further by identifying collaborative activities around game communities that might be able to facilitate language education. A scenario of an educational game community is presented and challenges in the use of such technologies in a game based setting are discussed.
Keywords: Constructionism; Game community; Language learning; Wiki technology